Determinants of Customer-based Brand Equity: A Study of Public and Private Banks. (August 2016) - Arora, Sangeeta; Neha,
The financial services sector has come a long way from arguing that banks are beyond branding to a phase where banks and other financial institutions are using branding strategically—like any other business. Banks have adopted various customer-centric strategies in order to develop a positive perception in the minds of customers. To develop and implement customer-centric strategies, banks need to provide a consistent brand experience to prevent customers from switching to rival banks. In order to understand the customer perception towards bank brand, there is a need to understand the concept of customer-based brand equity and its main determinants. The customer-based brand equity is a set of brand-related associations held by the consumers in their memory (Keller, 1993). The current article aims to identify the various determinants of customer-based brand equity in the banking industry and to verify whether these determinants vary across bank types. For this purpose, a structured questionnaire was developed and a sample of 120 respondents was taken from selected public sector banks and private sector banks of Jalandhar. Factor analysis produced six factors, that is, brand investments, brand performance, brand salience, brand verdict, brand feelings and brand unfamiliarity, which accounted for 73 per cent variance. The findings revealed that out of the six factors extracted from the study, brand verdict emerged as the most significant factor that led to the determination of customer-based brand equity. The results of independent sample t- test showed no significant differences in the perceptions of customers of public and private banks with respect to customer-based brand equity. Correlation analysis was also conducted on the study variables and the results indicated that there are strong, positive and significant relationships between brand performance and brand feelings, and between brand performance and brand verdict. The multiple regression results showed that only brand performance, brand salience and brand feelings have a significant influence on brand verdict, whereas brand investment had a significant negative impact on brand verdict.